Change of direction speed in youth male soccer players: the predictive value of anthropometrics and biological maturity - Negra, Y.; Sammoud, S.; Nevill, A. M.; Chaabene, H. (Pediatric Exercise Science, 2022)
This study aimed to develop the optimal allometric body size/shape and a biological maturity model that predicted the change of direction (CoD) mean speed performance in youth male soccer players. One-hundred and fifteen youth soccer players (age: 12.4 [1.3] y) participated in this study. The 505 test was used to assess CoD mean speed performance. Anthropometric measurements comprised body height (cm), sitting height (cm), body mass (kg), fat mass (kg), lower limb length (cm), thigh length (cm), leg length (cm), foot length (cm), thigh girth (cm), and calf girth (cm). The maturity status was determined based on the maturity offset method. To identify size/shape and maturity characteristics associated with CoD speed performance, we computed a multiplicative allometric log-linear regression model, which was refined using backward elimination. The multiplicative allometric model exploring the association between 505 CoD mean speed performance and the different anthropometric characteristics in youth soccer players estimated that fat mass (P < .001), sitting height (P = .02), and maturity offset (P = .004) are the key predictors. More specifically, youths who are more mature and have a lower fat mass and a shorter trunk length, are likely to achieve a better CoD mean speed performance. These findings highlight the relevance of considering anthropometric and maturity characteristics in youth soccer players to support talent identification.